Physical Properties of nickel coated brass copper alloy CZ121 by electro deposition process - Raad Rasool; Ahmad Said (College of Education for Pure Sciences, 2012)
Abstract This research which includes (copper alloys formation and studying of their physical properties). It has been tested both the rotating fatigue & hardness including their two types (shore & Vickers) for four CZ121 brass alloy states. The first state represents the uncoated standard brass alloy. The second one represents the coated alloy by Nickel by electro deposition process directly for 20 min duration. The third case represents the coated alloy by nickel too but after removing the stress at 275 . The last state was quenched alloy by water after heating to 875 for 45 min duration. All experiments were tested at the stress ration (R= -1). The results of fatigue test clarified that the coated alloy by Nickel after removing stress at 275 , characterized that it is the longest life because the stresses were removed and the cracks on its surface were filled by electro deposition, which has high ability to contact adhesion. Then the second best results were presented by the direct coated alloy by Nickel within the same electro deposition state. The third state according to its performance was CZ121 standard alloy without any change. The last one was CZ121 after heating it to 875 then quenched by water. Concerning the results of hardness test (shore ,Vickers) they can be arranged from the best as follow: the alloy electro deposition by Nickel the direct coating CZ121 alloy, the alloy electro deposition by Nickel after removing stress at 275 , the next was the standard CZ121 alloy without any effect on it, the last one was quenched alloy by water after heating at 875 as respectively.